Modelling, Monitoring, Control and Optimization for Complex Industrial Processes - Gao, Zhiwei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes 22 research papers and an editorial, collected from the Special Issue "Modelling, Monitoring, Control and Optimization for Complex Industrial Processes", highlighting recent research advances and emerging research directions in complex industrial processes. This reprint aims to promote the research field and benefit the readers from both academic communities and industrial sectors.